Maine Gov. James B. Longley: Don Quixote and Sir Thomas More, with a Dash of Machiavelli—An Appropriate Political DNA for the Day? - McGregor, Jim (Maine Policy Review, 2005)
Jim McGregor, Governor James B. Longley’s executive assistant during his term of office from 1975 to 1979, provides his reflections about Longley the man and the era in which he won election against all political odds to become Maine’s first independent governor. While many historians and State House observers concentrate on the “confrontational Longley,” McGregor sheds new and hitherto private light on the multifaceted Governor Longley and suggests he may have been a man ideal for the time during which he served.